Comparing Versions of the Good Behavior Game: Can a Positive Spin Enhance Effectiveness?. (July 2016) - Wahl, Elaine; Hawkins, Renee O.; Haydon, Todd; Marsicano, Richard; Morrison, Julie Q.
Disruptions can prevent the classroom from being an effective learning environment. The Good Behavior Game (GBG) is a group contingency that has been proven to effectively prevent disruptions and increase engagement. However, the traditional methods of the GBG include teacher scanning for negative student behaviors, and may not align with Positive Behavioral Interventions and Supports (PBIS), which is becoming widely adopted in many schools. Extending the findings of Wright and McCurdy, the current study compared the effects of the GBG and a positive version of the GBG, called the Caught Being Good Game (CBGG), on student behavior, including engagement and off-task behaviors, as well as teachers' use of positive and negative statements. Results showed both the GBG and the CBGG improved student behavior, with data not clearly indicating one was superior. Neither intervention led to an increase in positive teacher statements. Implications for teachers and suggestions for further research are discussed.